Multicomponent nucleation of malonic acid involved in the sulfuric acid - dimethylamine system and its atmospheric implications. (15th December 2021) - Wang, Zhong-Quan; Liu, Yi-Rong; Wang, Chun-Yu; Jiang, Shuai; Feng, Ya-Juan; Huang, Teng; Huang, Wei
Abstract: Malonic acid (MOA) is one of the main dicarboxylic acids in aerosols. Some field observations and experiments have revealed that malonic acid may be involved in new particle formation (NPF) events. However, there are few reports on the mechanism of atmospheric cluster formation involving MOA. In this study, high-precision quantum chemical calculations and dynamics simulations were used to investigate the mechanism by which MOA participates in a sulfuric acid (SA) - dimethylamine (DMA) multicomponent system. The most stable molecular structures show that MOA can form relatively stable clusters with the SA-DMA system by hydrogen bonding and proton-transfer interactions. Compared with the results of the CERN-CLOUD experiments, the formation rate of the SA-MOA-DMA system is between those of SA-DMA-W and SA–NH3 –W systems at high concentration of DMA. This means that nucleation of the ternary SA-MOA-DMA system cannot be ignored in atmospheric aerosol nucleation. It was also found that temperature was crucial to the formation rate of the SA-MOA-DMA system. The strong inverse relationship of the formation rate and temperature indicates that if the temperature decreases the ternary SA-MOA-DMA system becomes increasingly important in NPF events. Highlights: MOA may play an important role in particle formation and growth. The MOA molecule is similar to the SA molecule in providing protons to DMA. Formation rates are negatively correlated with temperature.